2019
DOI: 10.3390/nano10010027
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Angle Polarization-Independent Ultra-Broadband Absorber from Visible to Infrared

Abstract: We theoretically proposed and numerically analyzed a polarization-independent, wide-angle, and ultra-broadband absorber based on a multi-layer metasurface. The numerical simulation results showed that the average absorption rates were more than 97.2% covering the broad wavelength of 400~6000 nm (from visible light to mid-infrared light) and an absorption peak was 99.99%, whatever the polarization angle was changed from 0° to 90°. Also, as the incidence angle was swept from 0° to 55°, the absorption performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…Comparison of the absorption curves for the original model and the planar structure showed that the presence of an artificially designed cross-shaped resonator and a triangular array had a significant impact on the absorption bandwidth and peak. This was also supported by previous experimental results: absorbers with special shapes (e.g., disc) are more efficient than absorbers with stacked structures [22,28]. Fig.…”
Section: Resultssupporting
confidence: 86%
“…Comparison of the absorption curves for the original model and the planar structure showed that the presence of an artificially designed cross-shaped resonator and a triangular array had a significant impact on the absorption bandwidth and peak. This was also supported by previous experimental results: absorbers with special shapes (e.g., disc) are more efficient than absorbers with stacked structures [22,28]. Fig.…”
Section: Resultssupporting
confidence: 86%
“…Metamaterial absorbers play an important role in bioimaging, material detection, solar cells, communications, biosensing, and other fields. 12–26…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterial absorbers play an important role in bioimaging, material detection, solar cells, communications, biosensing, and other fields. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] At present, the design of absorbers mainly focuses on narrowband absorbers and broadband absorbers. Yang et al, 27 Li et al, 28 Nejat et al, 29 and others 30,31 introduced metal rectangles, gold cylinders, nested metal rings, and other metamaterial absorbers to achieve the perfect absorption of single frequency, dual-frequency, and narrowband frequencies in the THz range.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, previous studies have focused on the use of multilayered structures consisting of alternating layers of flat metal and dielectric plates as common infrared absorbers. The reason for this has to do with nature of the structure, which could broaden the absorption bandwidths [20][21]. For instance, Cui et al theoretically proposed a metamaterial PA with 20 metal-dielectric (M-D) layers, and predicted absorptions above 95% in the spectral range from 3000 to 5500 nm [16].…”
Section: Introductionmentioning
confidence: 99%